Desenvolvimento de liderança e o estudo dos programas institucionais - Maruyama, Andréa (2011)
Relevance of studies related to leadership has been highlighted in the academic field as well as inside organizations. As a result of this strategic relevance of this issue, have pushed academic researchers on definitions and studies related to Organizational Behavior which theories have been built in order to complement standards already defined in the literature. This situation builds a scenario whose scope one cannot find whole meaning of leadership issue. Definitions available are, from one side different among their shelf and, from the other side, complementary. However, two elements seem to be in a commonsense. First of all, leadership as a phenomenon linked to at least two individuals. Second, leadership has been considered as an influence process. Main definitions related to leadership were considered for this academic research which objective is to evaluate contents related to leadership programs in a bank organization. Analytical focus as based on actions made by this organization in order to develop their leaders, to manage teams and to build up strategy for leadership development. By considering amplitude of the object, subjectivity and its contemporary characteristic for business administration, a qualitative study was conducted in order to analyze phenomenon through a case study in an international bank that has played in Brazil since 1957 and nowadays is responsible for approximately 52 thousand employees and 38% of them in a leadership position. During the study, researcher could verify that this organization put in place corporative programs top develop leadership focus on day-by-day and strategic decision making processes